Photocatalytic degradation of dyes and microorganism inactivation using solution blow spun silver-modified titania fibers. Issue 9 (15th June 2020) - Leite, R.S.; Santos, A.M.C.; Severo, L.L.; Duarte Neto, J.F.; Castellano, L.R.C.; Neves, G.A.; Lira, H.L.; Menezes, R.R.
Abstract: This work investigated the photocatalytic effect of silver-modified titania fibers on the degradation of rhodamine B (RB) and methylene blue (MB) and the inactivation of Escherichia coli and Staphylococcus aureus strains. Fibrous cotton-wool-like structures resulted from a combination of the sol-gel route to solution blow spinning followed by calcination of hybrids fibers at 700 °C. Analysis of X-ray diffraction and transmission electron microscopy confirmed the presence of anatase and rutile polymorphs and metallic silver on fibers. Silver-modified titania fibers inhibited bacterial growth in all experimental conditions regardless of the ion content or UV-irradiation. The effectiveness of microorganism inactivation of titania fibers increases upon UV-irradiation. pH did not influence the photodegradation of RB, and solutions with basic pH enhanced the removal of MB. In a fixed pH, MB presents a faster photodegradation rate as compared to RB, but they match when applying silver-modified titania fibers and UV-irradiation.